2022
DOI: 10.3389/fsufs.2022.908018
|View full text |Cite
|
Sign up to set email alerts
|

A review of gender in agricultural and pastoral livelihoods based on selected countries in west and east Africa

Abstract: This scoping paper presents the results of a review of the landscape of research on gender and agricultural and pastoral livelihoods in select countries in west and east Africa (Burkina Faso, Chad, Eritrea, Ethiopia, Kenya, Mali, Mauritania, Niger, Nigeria, Sudan, South Sudan, Somalia, and Uganda) published over 5 years (January 2016–March 2021). A keyword search of the Scopus database gave rise to an ultimate dataset of 169 papers which were coded for geographical location, approaches to gender, and theme bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 185 publications
0
1
0
Order By: Relevance
“…In this discussion, we engage particularly with two literature reviews concerning the gendered nature of CCA practices within rural East African households that were published while we were conducting our review. [7,8] While neither of these articles focus primarily on CCA decision-making, their findings are adjacent to the issues studied in the present review. We then conclude by discussing implications for gender-responsive adaptation interventions.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In this discussion, we engage particularly with two literature reviews concerning the gendered nature of CCA practices within rural East African households that were published while we were conducting our review. [7,8] While neither of these articles focus primarily on CCA decision-making, their findings are adjacent to the issues studied in the present review. We then conclude by discussing implications for gender-responsive adaptation interventions.…”
Section: Discussionmentioning
confidence: 95%
“…Lastly, we encountered two challenges inherent in the field under study: First, as has been noted before, [8] the concept of CCA decision-making remains vague in many studies, and there appears to be no consensus about how decision-making should be assessed in qualitative and quantitative research. One study included in the present review found that perceptions of men's and women's involvement in intra-household CCA decisions differed greatly between male and female participants.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Gender-Oriented Development Pathway for the Gender Sensitive Endowed with Negative PsyCap Typology Gender has been highlighted as one of the factors that influence participation in agricultural activities (Glazebrook and Opoku 2020;Vincent 2022), with the same applicable to youth (Moreda 2020). The participation of females in agriculture is complicated by the array of roles they are expected to fulfil by society and societal norms, as well as beliefs about gender roles that do not include female participation in agricultural activities, as they are considered male activities (Theeuwen et al 2021;Vincent 2022). In addition, the biases in ownership, access and control of productive resources such as land, inputs and credit, in favour of males, also constrain active engagement of females in agricultural activities (Gebre et al 2021;Holden and Tilahun 2021;Ake et al 2020;Abubakar 2021).…”
Section: Marketmentioning
confidence: 99%